Exploring 2-metallacryptands and 2-metallacryptates with quantum chemical methods - When (not only) computer chemists' dreams come true - Puchta, Ralph; van Eikema Hommes, Nico; Seitz, Verena; Saalfrank, Rolf (Journal of Molecular Modeling, 2000)
Semiempirical PM3 computations are reported for the 2-gallium cryptand and 2-gallium cryptates with three 2,6-bis(acetylaceto)pyridine ligands. Optimized "sparkles" are employed for the description of metal ion guests for which no PM3 parameters are available. Calculated structures agree well with available X-ray structures of the corresponding 2-iron cryptates. The trend in the computed complexation energies of the guest metal ions, compared to solvent complexes, agrees with experimental findings: for experimentally known complexes, exothermic exchange is computed, while endothermic exchange is calculated for cryptates that could not be synthesized. In the case of lead, the predicted favorable cryptate formation subsequently was verified experimentally.
Keywords: supramolecular chemistry; metallacryptates; semiempirical calculations; sparkles